Idiopathic Pulmonary Hypertension and in Situ Thromboembolism: A Difficult Case in Clinical Practice - M. A. Us; Ju. Ju. Karpenko (Архивъ внутренней медицины, 2024)
Pulmonary hypertension is a complex syndrome for differential diagnosis, which is the outcome of various pathological conditions. With the exclusion of the two most common causes of pulmonary hypertension, such as pathology of the left heart chambers and pulmonary embolism, further search for etiology often becomes problematic. Despite the emergence of a number of international and domestic recommendations, as well as certain successes in drug therapy, the long-term prognosis in patients with pulmonary arterial hypertension remains unfavorable. In the description of this clinical case in a 39-year-old woman suffering from idiopathic pulmonary arterial hypertension, the main complaint of the patient was very non-specific. The woman could not bear the child, all her attempts, lasting more than 19 years, remained unsuccessful. Even in absolutely healthy women, pregnancy is associated with the highest risks and is a powerful “test” of the body, not to mention patients suffering from rare diseases. The patient has a “subacute” course and a fairly rapid progression of the disease with a significant deterioration in the quality of life, which led to the impossibility of carrying a pregnancy. There were also signs that aggravated the prognosis, such as increased dyspnea, loss of consciousness, a significant decrease in working capacity and a high degree of pulmonary hypertension (according to echocardiography, systolic pressure in the pulmonary artery > 128 mm Hg). Due to the ineffectiveness of standard therapy with a selective inhibitor of cycloguanosine monophosphate — specific phosphodiesterase type 5 — sildenafil; the option of specific therapy for pulmonary hypertension was considered, which made it possible to change the situation and bring the patient into a stable state and draw conclusions about the pregnancy.